Summit Lake on the White Pass & Yukon Railroad, British Columbia, approximately 1899. - Hegg, Eric A., 1867-1948 (1899)
Shows the Alaska-Canada boundry. Caption on image: "Summit Lake. White Pass and Yukon Route." Original image in Hegg Album 3, page 25. Original photograph by Eric A. Hegg 256; copied by Webster and Stevens 381.A. Klondike Gold Rush.